Optical Property Enhancement in Cobalt Doped Magnetite Nanoparticles Evaluated with UV Vis Tauc and Urbach - Saputra, Kormil; Ika Umratul Asni Aminy; Rahmatun Inayah; Teguh Ardianto; Dian W. Kurniawidi (UNIB Press, 2025)
Magnetite (Fe3O4) is a spinel-based material that has broad potential in various applications, one of which is for magneto-optics. However, the value of the energy gap obtained from magnetite is too small to be applied. Efforts to improve these characteristics are carried out through transition metal ion doping techniques, one of which is cobalt (Co2+) which is known to modify the electronic structure and stabilize the crystal lattice. This study aims to analyze the optical properties of magnetite nanoparticles that have been doped with Co2+ through energy gap and Urbach energy calculations. The synthesis of Co0.125Fe2.875O4 was carried out using the coprecipitation method. Furthermore, characterization was carried out using UV–Vis spectroscopy and analyzed the size of the energy gap and Urbach energy. The results showed that cobalt doping (Co0.125Fe2.875O4) produced two indirect energy gap values ​​of 2.07 eV and 3.19 eV and one direct energy gap value of 3.63 eV. Urbach energy analysis revealed a very low Eu value of 0.0073 eV, indicating high crystal regularity and minimal structural defects in the material. This study demonstrated that cobalt doping not only increases the band gap energy of magnetite but also significantly lowers the Urbach energy, resulting in a material with more pronounced optical properties.